ANALYSIS OF HEMATOLOGICAL VARIABLES AMONG COMPETITORS IN VARIOUS GAMES - Rahaman, Aminur (International Journal of Research -GRANTHAALAYAH, 2021)
Hematological factors may be useful in determining the best physical performance of various game participants. It also indicates the athletes’ health and physical condition. This study deals with the analysis of hematological variables-red blood cells, white blood cells (, eosinophil, lymphocytes, ), and platelet among university men basketball, volleyball, and cricket players. Fourteen (14) active players (basketball-5, volleyball-5, and cricket-4) were taken as samples and age range years. All players were actively competing at Inter-University levels in their respected they voluntarily participated in this study. Blood samples were collected in the morning session with fasting. Red blood cells, white blood cells, platelet counts were criterion measures in this study. The obtained data were analyzed by one-way ANOVA with the help of SPSS software and the level of significance was set at p<0.05. As per the statistical analysis, insignificant differences were found among the three different game players. In summary, the study found that the red blood cells, white blood cells, and platelet counts are similar in the three groups.